400 years of the science of psychology in Lithuanian schools - Plečkaitis , R. (Psichologija, 1973)
In Lithuania the science of psychology appeared during the feudal system. Those sons of Lithuanian noblemen became acquainted with the science first who studied at the universities of Central and Western Europe in the 14th-16th centuries. The origin of the science of psychology in Lithuania is closely connected with the Vilnius College founded in 1570. Since 1571 scholastic philosophy was taught there. Psychology was not an independent branch of philosophy. The treatise “About the Soul” was delivered as a separate course in physics. During the lectures Aristotle’s works on psychology were delivered to the college students first in 1574. Ioannes Hay, Scot professor of philosophy, was the first lecturer on psychology. Twenty-six printed theses on psychology maintained by the Vilnius College students during disputes in 1577-1578 have reached our days. In 1579 the college was reorganized into the University of Vilnius. The first extant lectures on psychology delivered at the Vilnius University date back to 1615-1616. In the first part of the 17th century psychology was not taught as a speculative science. Lecturers sought a material basis of psychological processes taking into account the views of the following Renaissance scientists - A. Vesalius, J. Fernelius, G. Rondelet, G. Fabricius, G. Fracastoro. Psychological concepts were analysed of the Italian Renaissance representatives: I. Zabarella, G. Cardano, F. Piccolamini, P. Pomponacci, also G. Pereira.